Exploring engineering students’ epistemic beliefs and motivation: A case of a South African university - Makhathini, T.P.; Mtsweni, S.; Bakare, B.F. (South African Journal of Higher Education, 2020)
This study seeks to investigate how chemical engineering students from South African low-income communities locate knowledge structures. The study used an existing Engineering Related Beliefs Questionnaire (ERBQ) to evaluate beliefs of 268 chemical engineering students. The questionnaire collects additional information by allowing open-ended responses on each item to increase reliability of the questionnaire. Findings suggest that more than 60 per cent of students believe that engineering knowledge cannot be argued, and that learning takes place only when the lecturer transmits knowledge. Engineering educators may consider a humanizing pedagogy, which create opportunities for students from low-income communities to be liberated and reduce the dependency culture. Application of this pedagogy may assist students to achieve life long learning whilst developing necessary soft skills like independent thinking and innovation.